Affective Urbanism: Building Urban Commons from Empty Buildings at Montevideo - Goñi Mazzitelli, Adriana (Sens public, 2024)
Home to 1.3 million inhabitants, the city of Montevideo, the capital of Uruguay, sits in a natural harbour with one of the most important ports of the region. The growth of the city follows in the last fifty years the deregulation of the housing market, and neoliberal urban policies, which create two phenomena: on one hand the gentrification and the abandon of central areas by the population and on the other hand the informal land occupations and self-construction initiatives in peripheries. In the last ten years social movements for the right of the city make pressure to make the government of the city understand the need to promote the replacement or recycling of empty buildings in traditionally central areas with public policies of social uses and housing. In 2019 was launched Reactor Ciudad Vieja an urban laboratory, guided by the applied research group in Participative and Affective Urbanism of the Faculty of Architecture, Design and Urbanism, in collaboration with the Program Empty Buildings of the Municipality of Montevideo. The laboratory aims to recover empty buildings transforming them into urban commons in the historic centre by participative processes among social movements, neighbours, university, and public offices. The results of the planning process were an Initial Agenda with proposals for the uses of the empty buildings, as well as the co-design and build of a pilot experience in a historic building. The process also accounts for the relevance of innovation in the associate management of the pilot experience among civil society and the Municipality of Montevideo. This experience confirms the relevance of the internationally recognized participatory methods in design and planning, which includes locating oneself in a particular context, thinking the habitat construction in an integrative way, starting from local histories and affections, proposing creativity in the methods to make social movements organization emerge and produce innovative results in terms of material and immaterial quality and redistribution of responsibilities in implementation and management of civic uses in the city.